New Approach to the Yakut Language Dictionary: Preface as Paratext - Elena Stepanovna Rufova (Qubahan Academic Journal)
This article investigates the communicative and pragmatic potential of the lexicographic preface, with a focus on the preface to the Dictionary of the Yakut Language by E.K. Pekarsky (1907), which creation is associated with the Sibiryakov’s (Yakut) expedition of the Imperial Russian Geographical Society (1894-1896). Publishing of this dictionary is determined as a significant scientific fact for researchers of the issues of Yakut linguistics in the context of the scientific paradigm of Russian Turkology. The present study aims to explore the historical, social, and cultural factors influencing the creation of the preface, using a socio-pragmatic and anthropocentric approach. The research utilizes contextual, comparative, and source analysis methods to examine how paratextual elements in the preface shape the reader’s understanding of the dictionary. By analyzing Pekarsky’s rhetorical strategies, such as his self-presentation and engagement with the reader, the study reveals how the preface communicates the significance of the dictionary’s creation. The findings underscore the informative-pragmatic function of the preface, highlighting its role in conveying historical and research insights into the development of the Yakut-Russian dictionary. Ultimately, the preface serves as a key paratext that informs the reader about the lexicographic and historical context of the dictionary.